Stamp duty on shares and its effect on share prices - Steve Bond; Mike Hawkins; Alexander Klemm (Institute for Fiscal Studies (IFS), 2004)
This paper provides a discussion of stamp duty and its effects. This is followed by an empirical study using changes in the rate of stamp duty in the UK as natural experiments. Because shares will be affected differently depending on how frequently they are traded, we can employ a difference-in-differences methodology. We find that the announcements of cuts in stamp duty had a significant and positive effect on the price of more frequently traded shares compared to other shares. As expected under the efficient markets hypothesis, the implementation of cuts (when at a different date from the announcement) did not affect returns differentially.
Keywords: G14; H29; E62; 330; Stamp duty; transaction tax; Tobin-tax; natural experiment; tax reform; Börsenumsatzsteuer; Börsenkurs; Tobinsteuer; Großbritannien